Curriculum design under a new Ofsted regime. (2nd May 2019) - Bromley, Matt
Abstract : The new Ofsted inspection framework will see a focus on the breadth of a school's curriculum offer, including its 'intent', 'implementation' and 'impact'. In light of these changes, Matt Bromley looks at how schools might plan their curriculum